What's Happening in Leadership? (Carrick Institute for Learning and Teaching in Higher Education, 2007)
This document provides information on the leadership projects of the Australian Learning and Teaching Council (ALTC). The Leadership for Excellence in Learning and Teaching Program aimed to strengthen leadership and build the capacity to lead change for the future enhancement of learning and teaching in Australian higher education. The program has several different strands which focus on the institutional, discipline-based and specific project levels. This document lists the current projects.